Opioid-free total intravenous anesthesia for thyroid and parathyroid surgery: Protocol for a randomized, double-blind, controlled trial - Wang, Dan; Long, Yu-qin; Sun, Yan; Zhu, Ya-juan; Feng, Xiao-mei; Liu, Hong; Ji, Fu-hai; Peng, Ke (Frontiers in Medicine, 2022)
Background: Opioid-free anesthesia (OFA) may improve postoperative outcomes by reducing opioid-related adverse effects. This study aims to evaluate the effects of OFA on postoperative nausea and vomiting (PONV), postoperative pain, and 30-day outcomes after thyroid and parathyroid surgery. Methods: This two-center, randomized, double-blind, controlled trial will include 400 adult patients scheduled for thyroid and parathyroid surgery. Patients will be randomly assigned, 1:1 and stratified by sex and site, to an OFA group (esketamine, lidocaine, and dexmedetomidine) or a control group (opioid-based anesthesia with sufentanil). All patients will receive propofol-based total intravenous anesthesia and PONV prophylaxis with dexamethasone and ondansetron. The primary outcome is the incidence of PONV (defined as experiencing any event of nausea, retching, or vomiting) during the first 48 hours postoperatively. The secondary outcomes include the severity of PONV, antiemetic rescue therapy, pain scores at rest and while coughing, need for rescue analgesia, perioperative adverse effects related to anesthetics or analgesics (hypotension, bradycardia, hypertension, tachycardia, desaturation, dizziness, headache, hallucination, and nightmare), time to extubation, length of post-anesthesia care unit stay, length of postoperative hospital stay, patient satisfaction, and a composite of 30-day major adverse events (myocardial infarction, cardiac arrest, cerebrovascular accident, coma, acute renal failure, pulmonary embolism, sepsis, septic shock, deep neck space infection, reintubation, reoperation, blood transfusion, failure to wean off ventilator, and death). Analyses will be performed in the modified intention-to-treat population. Discussion: We hypothesize that our OFA regimen reduces PONV after thyroid and parathyroid surgery. We will also investigate whether OFA leads to improvements in postoperative pain and major adverse events. Our results will offer evidence for optimizing anesthesia regimens in patients who undergo thyroid and parathyroid surgical procedures. Trial registration: Chinese Clinical Trials Registry (Identifier: ChiCTR2200059656)